A study of occupational stress and coping strategies among correctional officers in Kedah, Malaysia - Mohd Zukri I,; Noor Hassim I, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
The effect of stress among correctional officers at the workplace can contribute to various health problems and this also affect their work performance and motivation. Methodology : Study was done at a prison located at the rural district in Kedah. The study was conducted by using randomized stratified sampling method. A total of 418 self administrated questionnaires were distributed. These questionnaires included socio demographic factor, family and marriage factor, Personal Stress Inventory (using Stress Symptom Scale with 52 items), work related stressors (Job Stress Survey) and Brief COPE (Coping Orientation for Problems Experienced with 28 items). Result : Response rate was 90.9%. Stress prevalence for correctional officers was 45.8%. Socio demographic factors which have significant relation with stress status were marital status, promotion factor, age, monthly salary, duration of service and number of children (p< 0.05). Family and marriage factor which have significant relation with stress status among married officer were pressure from relatives, clean up house, sexual frustration, conflict with spouse, conflict with children, conflict due to household work and no babysitter (p< 0.05). Discussion : The study showed that work related stressors that have influence with stress were excessive workload, working after work hours, not enough staff, disgraced words from fellow workers, competition in carrier development and excessive work stress (p< 0.05). Multiple linear regression model was done in this study and revealed factors that explained 52% of variation in stress score distributions were behavioural disengagement, no babysitter, denial, conflict with children, replace other worker’s duty, not enough time with family, competition in carrier development, venting of emotion, positive reframing and emotional support. Coping strategies that have significant effect in reducing stress symptoms are positive reframing and emotional support. Conclusion : Stress management programs should be implemented and emphasizing on specific stressors and coping mechanism are important to reduce the risk of occupational stress among correctional officers.